ASUHAN KEBIDANAN KOMPREHENSIF NY ”L” DI KLINIK UTAMA BUNDA PUJA TAHUN 2021 - Karmila, Karmila (Jurnal Kesehatan Husada Gemilang, 2022)
In the third trimester of pregnancy, the mother complains of nausea and frequent urination. The cause of nausea in mothers is the size of the uterus is getting bigger which can cause pressure on the stomach and back up into the esophagus, causing nausea during late pregnancy and increased production of the hormone progesterone which can trigger nausea in the mother. Frequent urination is caused by the fetal head starting to descend downward, causing pressure on the bladder and causing the mother to urinate frequently. Based on the theory, the complaints felt by the mother are physiological and can still be overcome. This Final Project Report is a comprehensive midwifery care carried out for Mrs. L G4P3A0H3 39-40 weeks of pregnancy which was carried out on 09 February 2021 to 28 March 2021 from the 3rd trimester of pregnancy, childbirth, postpartum, BBL, to family planning which was documented with implementation of varney management and SOAP documentation. The results of comprehensive midwifery care in the delivery process have gaps, namely internal examinations that are carried out irregularly and there are no indications when conducting internal examinations. Meanwhile, according to the theory, internal examination is carried out every 4 hours unless there is an indication. In spacing pregnancies and family planning counseling has been done, the mother chooses to use the pill. It is recommended that midwives can improve comprehensive midwifery care in providing quality and quality services. Pada kehamilan Trimester 3 ibu mengeluh mual-mual dan sering kencing. Penyebab rasa mual pada ibu yaitu ukuran rahim semakin besar yang dapat menyebabkan tekanan pada lambung dan naik kembali ke kerongkongan sehingga menyebabkan mual saat hamil tua serta meningkatnya produksi hormon progesterone yang bisa memicu rasa mual pada ibu. Sering kencing disebabkan kepala janin sudah mulai turun kebawah, sehingga terjadi penekanan pada kandung kemih dan menyebabkan ibu sering kencing. Berdasarkan teori keluhan yang dirasakan ibu merupakan fisiologis dan masih bisa diatasi. Laporan Tugas Akhir ini merupakan asuhan kebidanan komprehensif yang dilakukan pada Ny.L G4P3A0H3 usia kehamilan 39-40 minggu yang dilaksanakan pada tanggal 09 Februari 2021 sampai tanggal 28 Maret 2021 dari masa kehamilan trimester 3, bersalin, nifas, BBL, sampai KB yang didokumentasikan dengan penerapan manajemen varney dan pendokumentasian SOAP. Hasil dari asuhan kebidanan secara komprehensif pada proses persalinan terdapat kesenjangan yaitu pemeriksaan dalam yang dilakukan secara tidak teratur serta tidak ada indikasi saat melakukan pemeriksaan dalam. Sedangkan menurut teori pemeriksaan dalam dilakukan setiap 4 jam sekali kecuali adanya indikasi. Dalam menjarakkan kehamilan dan sudah dilakukan konseling KB, ibu memilih untuk menggunakan KB pil. Disarankan kepada bidan dapat meningkatkan asuhan kebidanan secara Komprehensif dalam melakukan pelayanan yang berkualitas dan bermutu.